Analysis of canine gene constraint identifies new variants for orofacial clefts and stature - Buckley, Reuben M.; Bilgen, Nüket; Harris, Alexander C.; Savolainen, Peter; Tepeli, Cafer; Erdoğan, Metin; Serres Armero, Aitor; Dreger, Dayna L.; van Steenbeek, Frank G.; Hytönen, Marjo K.; Parker, Heidi G.; Hale, Jessica; et al.

(untitled) (Genome Research, 2025)
Dog breeding promotes within-group homogeneity through conformation to strict breed standards, while simultaneously driving between-group heterogeneity. There are over 350 recognized dog breeds that provide the foundation for investigating the genetic basis of phenotypic diversity. Typically, breed standard phenotypes such as stature, pelage, and craniofacial structure are analyzed through genetic association studies. However, such analyses are limited to assayed phenotypes only, leaving difficult-to-measure phenotypic subtleties easily overlooked. We investigated coding variation from over 2000 dogs, leading to discoveries of variants related to craniofacial morphology and stature. Breed-enriched variants were prioritized according to gene constraint, which was calculated using a mutation model derived from trinucleotide substitution probabilities. Among the newly found variants is a splice-acceptor variant in PDGFRA associated with bifid nose, a characteristic trait of Çatalburun dogs, implicating the gene's role in midline closure. Two additional LCORL variants, both associated with canine body size are also discovered: a frameshift that causes a premature stop in large breeds (>25 kg) and an intronic substitution found in small breeds (<10 kg), thus highlighting the importance of allelic heterogeneity in selection for breed traits. Most variants prioritized in this analysis are not associated with genomic signatures for breed differentiation, as these regions are enriched for constrained genes intolerant to nonsynonymous variation. This indicates trait selection in dogs is likely a balancing act between preserving essential gene functions and maximizing regulatory variation to drive phenotypic extremes.